Finansowe kulisy walki o polską koronę po abdykacji Jana Kazimierza, a przed elekcją Michała Korybuta Wiśniowieckiego w świetle raportów dyplomatów elektora brandenburskiego (1668–1669) - Kaniewski, Jacek (Przegląd Nauk Historycznych, 2005)
In the presented article, the author has concentrated on the presentation of the backroom activities of the brandenburgian elector's diplomats who resided in the Republic of Poland in the years 1668-1669. The main diplomats of the elector Friedrich Wilhelm Hohenzollern in that time were: Johann von Hoverbeck, Joachim Scultetus, Eusebius Brandt and Friedrich Jena. In the article there is shown an elaborate diplomatic game and actions using money and given promises to acquire political allies who would declare themselves for a candidate to a Polish crown - prince Philip Wilhelm Neuburg - supported by Friedrich Wilhelm Hohenzollern and Ludwik XIV. Branderburgian-Prussian diplomats were leading talks, meeting the former king, Jan Kazimierzand officials of high rank to test their opinion and eventually pull them on their side. There is shown in the article that one of the ways to acquire political allies in the election fight was corruption used by foreign diplomats. The author, using the archival sources has presented diplomatic activities, in which money or a promise of a grace or an office was a price for received support or service. It was possible to examine what sums of money were offered in these political auctions and to whom they were given, how people who were interested were increasing prices by themselves, sometimes playing on both sides. There is presented a game of elector Friedrich Wilhelm's diplomats, tending not only to corrupt magnates and important officials on the election time, but also they were trying to gain long-range aims by winning persons in high positions in the authority and official hierarchy and on this way to gain precious and secret information about Polish politics. The political result of the election was unexpected, as the nobility has rejected foreign candidates to choose the native one - 19th June 1669 the prince Michał Korybut Wiśniowiecki was elected to be a king of Poland. A big group of nobility were showing hostility toward backroom activity of senators and diplomats and a corruption used by them. It is worth to pay attention that the estimation of a new monarch by the elector's diplomats was very quick. They decided that a choice of him would not be unprofitable for the elector what was a very clear proof that the Friedrich Wilhelm's politics toward Poland was negative. In the conclusion, the author presented the then estimation of the corruption issue and opinions of contemporary academics who investigate this problem.